(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Lesbian, gay, and bisexual people in romantic relationships suffer stigma, prejudice, and discrimination resulting from pervasive societal devaluing of same-sex partnerships. Research on same-sex couples has shown a negative connection between feelings of stigma and relationship quality. However, important issues remain unresolved about how feelings of stigma become more or less relevant within the setting of same-sex partnerships. This article provides a study of the tales that a purposive sample of 99 people in same-sex relationships wrote about their relational high points, low points, choices, and aspirations, as well as their experiences of stigma directly linked to their relationships. Narrative analysis of these tales showed that participants used various psychological techniques for making sense of their experiences of stigma within the framework of their relationships. Some participants viewed stigma as having a detrimental effect on their relationships, while others saw stigma as important, but external to their lives. Some participants viewed stigma as offering a chance to redefine concepts of commitment and relationship validity. Additionally, several participants viewed stigma as bringing them closer to their spouses and deepening the connection within their relationships. The findings of this research reveal the psychological methods people in same-sex couples employ to make sense of, deal with, and overcome social devaluation thus improving understandings of the connection between stigma and intimacy within disadvantaged partnerships.